Thermal analysis and microstructure of Portland cement-fly ash-silica fume pastes - Chaipanich A. (2014)
Thermal analysis (thermogravimetry and differential thermal analysis) was used with scanning electron microscopy technique to investigate the hydration mechanisms and the microstructure of Portland cement-Fly ashsilica fume mixes. Calcium silicate hydrate (C-S-H), ettringite, gehlenite hydrate (C 2ASH8), calcium hydroxide (Ca(OH)2) and calcium carbonate (CaCO3) phases were detected in all mixes. In the mixes with the use of silica fume addition, there is a decrease in Ca(OH)2 with increasing silica fume content at 5 and 10% compared to that of the reference Portland-fly ash cement paste and a corresponding increase in calcium silicate hydrate (C-S-H).